2019
DOI: 10.1038/s41598-019-41140-1
|View full text |Cite
|
Sign up to set email alerts
|

The polyadenylation inhibitor cordycepin reduces pain, inflammation and joint pathology in rodent models of osteoarthritis

Abstract: Clinically, osteoarthritis (OA) pain is significantly associated with synovial inflammation. Identification of the mechanisms driving inflammation could reveal new targets to relieve this prevalent pain state. Herein, a role of polyadenylation in OA synovial samples was investigated, and the potential of the polyadenylation inhibitor cordycepin (3’ deoxyadenosine) to inhibit inflammation as well as to reduce pain and structural OA progression were studied. Joint tissues from people with OA with high or low gra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
43
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 30 publications
(44 citation statements)
references
References 61 publications
0
43
1
Order By: Relevance
“…As cordycepine is similar to adenosine in structure, it can inhibit processes in which adenosine is involved (Xia et al 2017). Cordycepin reduces osteoarthritis symptoms, i.e., synovial inflammation, joint pathology, and pain behavior (Ashraf et al 2019). It has been proved that cordycepin inhibits senescence of cells in rodents through the NRF2 (nuclear factor erythroid 2-related factor 2) and AMPK (AMP-activated protein kinase) pathways in the inflammatory process.…”
Section: Secondary Metabolites: Role In Infection and Possible Applicmentioning
confidence: 99%
“…As cordycepine is similar to adenosine in structure, it can inhibit processes in which adenosine is involved (Xia et al 2017). Cordycepin reduces osteoarthritis symptoms, i.e., synovial inflammation, joint pathology, and pain behavior (Ashraf et al 2019). It has been proved that cordycepin inhibits senescence of cells in rodents through the NRF2 (nuclear factor erythroid 2-related factor 2) and AMPK (AMP-activated protein kinase) pathways in the inflammatory process.…”
Section: Secondary Metabolites: Role In Infection and Possible Applicmentioning
confidence: 99%
“…Reports include claims of efficacy in animal models of bone loss 23 , vascular disorder 24 , cognitive dysfunction 25 , sleep disorders 26 , cancer 21,27 , neuronal degeneration 28 , hyperlipidaemia 29 , oxidative stress 30 , hyperglycaemia 31 , asthma and lung inflammation 32 and viral infection 33 . Indeed, we have recently shown that oral cordycepin is effective in rodent models of osteoarthritis and demonstrated that it acts as an anti-inflammatory pain killer 34 . However, there seems to be lack of data on absorption and disposition of cordycepin as only extremely limited information can be found in the literature 35,36 .…”
Section: Introductionmentioning
confidence: 99%
“…As is the case for adenosine and its analogues, oral absorption and bioavailability of cordycepin is not well understood, despite multiple in vivo pharmacology studies performed with oral administration and the oral route being the intended route of administration for cordycepin 2325,27,29,34,37,38 . The information on the oral absorption processes and the biotransformation of cordycepin is critical in elucidating the exposure-effect relationship, especially given that there is strong evidence that cordycepin needs to be converted to cordycepin 5′-triphosphate (CordyTP) in order to exert at least some of its pharmacological effects 19,3941 .…”
Section: Introductionmentioning
confidence: 99%
“…Cordycepin suppresses proliferation and activates apoptosis in human epithelial endometriotic cells in vitro [406]. Osteoarthritis patients exhibit elevated CPSF4 expression, resulting in high levels of inflammatory genes [407]. Cordycepin has also been shown to reduce inflammatory gene induction in cell culture [408], and symptoms in rodent models of osteoarthritis [407].…”
Section: Targeting Mrna 3 End Formation As a Novel Therapymentioning
confidence: 99%